2011
DOI: 10.1093/brain/awr206
|View full text |Cite
|
Sign up to set email alerts
|

Central role of JC virus-specific CD4+ lymphocytes in progressive multi-focal leucoencephalopathy-immune reconstitution inflammatory syndrome

Abstract: Progressive multi-focal leucoencephalopathy and progressive multi-focal leucoencephalopathy-immune reconstitution inflammatory syndrome are caused by infection of the central nervous system with the JC polyoma virus. Both are complications of monoclonal antibody therapy in multiple sclerosis and other autoimmune diseases. Progressive multi-focal leucoencephalopathy-immune reconstitution inflammatory syndrome can obscure the diagnosis of progressive multi-focal leucoencephalopathy and lead to severe clinical di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 56 publications
2
106
1
1
Order By: Relevance
“…In a previous study, we reported the ability of some VP1-specific CD4 + T cells to secrete simultaneously IFN-g and IL-4, which we termed a Th1-2 phenotype (36). Cytokine release by the 14 braininfiltrating, VP1-specific CD4 + TCCs after in vitro stimulation with specific peptide was determined by ELISA (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study, we reported the ability of some VP1-specific CD4 + T cells to secrete simultaneously IFN-g and IL-4, which we termed a Th1-2 phenotype (36). Cytokine release by the 14 braininfiltrating, VP1-specific CD4 + TCCs after in vitro stimulation with specific peptide was determined by ELISA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we had established-from an MS patient who had developed PML-IRIS under natalizumab treatment-several brain-infiltrating, JCV-specific CD4 + TCCs that recognized different peptides of the major capsid protein of JCV, VP1 (36). Toward this aim, brain-derived, PHA-expanded mononuclear cells were seeded with autologous PBMCs and VP1 protein.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations